Aspek-Aspek Pertimbangan dalam Berkarir Sebagai Akuntan Publik - Amalia Suryani; Zaky Machmuddah (Jurnal Akuntansi Bisnis, 2018)
This study aims to prove empirically the effect of financial rewards, labor market considerations, professional training, work environment, professional recognition, and social value on career interests as public accountants. The population of this study isungraduate accounting students of 2014 amounts of 743 students and is obtained samples of 260 students. The obtained are data categorized as primary data getting by distributing questionnaires and secondary data. The test results prove that the professional training, work environment, professional recognition, and social value have significant effects on career interests as public accountants, unlike the variables of financial presentation and labor market considerations, the test results prove that those variables have no effect on career interest as public accountants